Ovine COX-1 Isoenzyme Bio-production - Miciaccia, Morena; Iaselli, Mariaclara; Ferorelli, Savina; Loguercio Polosa, Paola; Perrone, Maria G.; Scilimati, Antonio (Current Enzyme Inhibition, 2022)
Background: Recent findings enlightened the pivotal role of cyclooxygenases-1 and -2 (COX-1 and COX-2) in human diseases with inflammation as the committed earliest stage, such as cancer and neurodegenerative diseases. COXs are the main targets of nonsteroidal anti-inflammatory drugs and catalyze the bis-oxygenation of arachidonic acid into prostaglandin PGH2, then converted into prostaglandins, thromboxane, and prostacyclin by tissue-specific isomerases. A remarkable amount of pure COX-1 is necessary to investigate COX-1 structure and function, as well as for in vitro disease biochemical pathway investigations. Methods: Spodoptera frugiperda cells were infected with Baculovirus that revealed to be an efficient expression system to obtain a high amount of ovine(o)COX-1. Protein solubilization time in the presence of a non-ionic detergent was modified, and a second purification step was introduced. Results and Discussion: An improvement of a previously reported method for pure recombinant oCOX-1 production and isolation has been achieved, leading to a lower starting volume of infected cells for each purification, an increased cell density, an increased number of viral particles per cell, and a shortened infection period. The protocol for the recombinant oCOX-1 expression and purification has been in-depth elaborated to obtain 1 mg/L of protein. Conclusion: The optimized procedure could be suitable for producing other membrane proteins as well, for which an improvement in the solubilization step is necessary to have the availability of high concentration proteins.
Keywords: Cyclooxygenase (COX)-1